2020
DOI: 10.1021/acsapm.0c00874
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibers as a Delivery System for Arbuscular Mycorrhizal Fungi

Abstract: Arbuscular mycorrhizal fungi (AMF) are beneficial symbiotic organisms that play an important role in the water absorption and nutrient assimilation for a wide variety of plants. In this work, the use of polyethylene oxide (PEO) nanofibers was studied as a delivery system for AMF through the coated nanofibers of common bean seeds (Phaseolus vulgaris L var. José Beta). Thus, the effect of PEO nanofibers on the infective capacity of AMF and the indicator parameters of plant growth promotion (height plant, root l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Seeds are then wrapped within the inoculated fiber sheets. 59 Adapted with permission from ref. 58, 59 and 105. Copyrights 2019, 2020 American Chemical Society.…”
Section: Electrospun Nanofibrous Seed Coatingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seeds are then wrapped within the inoculated fiber sheets. 59 Adapted with permission from ref. 58, 59 and 105. Copyrights 2019, 2020 American Chemical Society.…”
Section: Electrospun Nanofibrous Seed Coatingsmentioning
confidence: 99%
“…107 Adapted with permission. 59,104,106,107 Copyrights 2019, 2020 American Chemical Society, Elsevier 2018, and Springer Nature 2020.…”
Section: Electrospun Nanofibrous Seed Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Halloysite-doped mycelial architectures were formed by immersing Aspergillus fumigatus pellets in halloysite nanotube-dispersed water. Campaña and Arias 66 investigated the use of nanofibers of poly(ethylene oxide) (PEO) as a transport system for arbuscular mycorrhizal fungi (AMF) through the production of coated bean seeds. The results of the study showed that PEO nanofibers have no negative effect on the infectivity of AMF.…”
Section: Overview Of Nanomaterials Used In Mycelium-reinforced Nanocompositesmentioning
confidence: 99%